Enhancing Attractiveness of Kampoeng Heritage Kajoetangan Malang: Developing Bilingual, QR-Code Assisted Website - Rohani, Siti; Fikron Nisa’, Zainab; Wahyu Wibowo, Dimas; Maulidiyah, Fitrotul; Sekarsari, Putri; Hanayeen, Nadia (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Increasing tourism sector as an effort to improve the economy can be done in several ways, including increasing the accessibility of favored tourist destinations. This increase in accessibility includes access to information in two languages, namely Indonesian and English as well as developing digital information of the tourism site. This article presents the development of a bilingual and QR-Code assisted website of Kampoeng Heritage Kajoengan (KHK), a tourist attraction located in Malang city with the main aim to improve the attractiveness of the site. The community service was done following a research design of design and development design, comprising stages of analysis, design and development, expert validation, and evaluation. Data were collected through direct observation, questionnaires, and interviews with the respondents of visitors and potential visitors of KHK, community management of KHK, and IT experts. Evaluation on the developed website was carried out, and it could be concluded that the website development for the KHK is quite successful. The website design was considered attractive; the use of two languages could be accessed easily. The website was easy to access and the presentation of information in English and Indonesian was considered quite informative. QR codes worked well and could be scanned and accessed easily. Overall, the website was considered very useful and could attract tourists to visit KHK directly.